Speech text of signing ceremony memorandum of agreement between Universiti Teknologi MARA and St. Thomas College of Engineering and Technology, Kerala, India / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
This MoA is an initiative under our existing MoU that represents the commitment of both institutions to work towards common goals in staff mobility and student exchange programmes. It represents a shared vision, mission, and responsibility that will positively impact our institutions. The partnership with St. Thomas College of Engineering and Technology is indeed fitting and timely.